2001
DOI: 10.1002/bip.1012
|View full text |Cite
|
Sign up to set email alerts
|

7Li‐NMR and FTIR studies of lithium, potassium, rubidium, and cesium complexes with ionophore lasalocid in solution

Abstract: Lasalocid metal salts were combined with 1 : 1 lithium and 2:2 potassium, rubidium, and cesium to form complexes. The nature of the lasolocid salt complexes was studied in a solid and chloroform by FTIR spectroscopy in the middle and far IR regions. The process of the complexation of lithium was also studied by (7)Li-NMR. In chloroform a 1 : 1 complex of lasalocid and Li(+) ions was formed. Continuous absorption was observed in the far FTIR spectrum of this complex. It indicated large Li(+) polarizability, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This means that the presence of the oxaalkyl chain affects the complex formation, especially with the Na + cations. In earlier studies the formation of 2:2 Na + lasalocid complexes was found 39, 40…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This means that the presence of the oxaalkyl chain affects the complex formation, especially with the Na + cations. In earlier studies the formation of 2:2 Na + lasalocid complexes was found 39, 40…”
Section: Resultsmentioning
confidence: 91%
“…We recently studied the nature of the complexes between lasalocid and monovalent cations by 7 Li‐NMR, 23 Na‐NMR, and FTIR spectroscopy 39, 40. In chloroform the formation of a 1:1 complex of lasalocid with Li + ions and 2:2 complexes of lasalocid with Na + , K + , Rb + , and Cs + ions was established.…”
Section: Introductionmentioning
confidence: 99%
“…In the spectrum of the lithium cation complex, we observe a shift in the absorption maximum towards lower wavenumbers by 4 cm −1 . This shift is slightly larger than those of the other cations, but still small compared to those of the other lasalocid acid esters studied earlier [9,11]. This shows that, in the case of such strongly hydrophilic derivatives of lasalocid acid (LasGlu and LasX), the keto group is only slightly involved in the formation of the complex.…”
Section: Ft-ir Measurementsmentioning
confidence: 63%
“…Even slight structural modifications [ 8 , 9 , 10 , 11 , 12 , 13 ] of the antibiotic molecules may result in changes to the structure of the complex, which affects the ability of the ionophore to bind metal ions and transport them through the cell lipid layers. For biologically active compounds, such changes may have an impact on their antimicrobial properties [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the many desirable properties, characterized by high toxicity. Receiving lasalocid acid derivatives, can lead to a reduction of its harmfulness, and thus increase its use 2001;2007;. (Berger et al, 1951).…”
Section: Introductionmentioning
confidence: 99%